DESIGNING A GENDER-RESPONSIVE QIRA’AH‎ LEARNING MODULE: ‎BRIDGING EQUALITY AND INCLUSIVITY IN ISLAMIC ‎HIGHER EDUCATION - Erlina, Erlina; Koderi, Koderi; Sufian, Muhammad (Universitas Islam Negeri Ar-Raniry, 2025)
The lack of gender-responsive learning materials causes biased understanding and does not support the principle of gender equality in Islam. Therefore, developing a gender-responsive qira’ah learning module aligned with gender equality principles represents an innovative approach to curriculum development. This research aims to design and test a gender-responsive qira’ah ‎ learning module for Islamic higher education using the research and development method and the ADDIE model, representing an innovative effort in curriculum development. The research results indicate that this gender-responsive qira’ah ‎ learning module significantly enhances students understanding of gender equality in the context of Islam. This is evidenced by an increase in the average score from 47,5 on the pre-test to 82 on the post-test, a gain of 34,5 points with a t-test yielding a p-value of 0.00, confirming that the improvement is statistically significant. The design of the module that integrates gender equality values, examples of the use of inclusive, non-stereotypical language, encouraging active student participation has created an inclusive learning environment. This is one aspect of the novelty of the results of this research. This module is expected to be a model for developing a qira’ah‎ curriculum that is more relevant and responsive to gender issues.